STUDENTS’ PERCEPTIONS OF USING NUMBERED HEAD TOGETHER (NHT) LEARNING MODEL TO IMPROVE STUDENTS’ SPEAKING ACHIEVEMENTS - Kusuma, Dewinta Dwi; P, Laili Rahma Dewi; Agustina, Eliasanti (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2025)
This article investigated students' perceptions after implementing the NHT learning model and the effectiveness of the NHT Learning model in improving students' speaking skills. This study used a qualitative method. Data were collected using a questionnaire containing 11 questions. The data source in this research is class X, totaling 40 students for the 2022/2023 academic year. To analyze the data, a qualitative descriptive method was used. The results show that the majority of students consider the NHT learning model to be fun, easy to use, and effective in improving speaking skills, self-confidence, and vocabulary. Student activities increased during teaching sessions, which shows that most students were involved and enthusiastic in learning. learning process. The Numbered Head Together (NHT) technique was proven to improve speaking skills and increase student achievements. NHT improved students’ speaking skills, self-confidence, and vocabulary, as well as facilitating group discussion and conveying thoughts.